If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x(x + 2) = 4x + 8 Reorder the terms: 4x(2 + x) = 4x + 8 (2 * 4x + x * 4x) = 4x + 8 (8x + 4x2) = 4x + 8 Reorder the terms: 8x + 4x2 = 8 + 4x Solving 8x + 4x2 = 8 + 4x Solving for variable 'x'. Reorder the terms: -8 + 8x + -4x + 4x2 = 8 + 4x + -8 + -4x Combine like terms: 8x + -4x = 4x -8 + 4x + 4x2 = 8 + 4x + -8 + -4x Reorder the terms: -8 + 4x + 4x2 = 8 + -8 + 4x + -4x Combine like terms: 8 + -8 = 0 -8 + 4x + 4x2 = 0 + 4x + -4x -8 + 4x + 4x2 = 4x + -4x Combine like terms: 4x + -4x = 0 -8 + 4x + 4x2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-2 + x + x2) = 0 Factor a trinomial. 4((-2 + -1x)(1 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-2, 1}
| (X+5)+(2x+5)=70 | | 2(x+1)=5[x-(3-x)] | | 2x+x=287.35 | | -3y^2-x^2+2xy-1=0 | | 12=7+15 | | 0=20-5t-5t^2 | | 4+6x-3-2x=5 | | 20=7+30t-16t^2 | | 3x^2-2xy-y^2+1=0 | | 2n^2-16+32= | | 2(3s+10)=74 | | 4x+8=8x-68 | | 8(2e+3)=40 | | 2400=(x*.76)+(y*.4) | | 4+3x=7+2x-3 | | X-11x=-28 | | 10x^2+27+5=0 | | (8x-5)+(-2x+7)= | | x=e^5y | | 014x+0.9(x-2)=0.01(4x-2) | | 24*.75x=18x | | Log(6x+4)=2 | | 5(a-10)=45 | | 16=103a | | 24*.75y=18y | | 2x+49x-9x+21x+5x= | | (6x+4)=2 | | (u+4)10=80 | | 3+4=6x+x | | 4y+5=3(2y-7) | | 9(18x-3)= | | (q-9)4=8 |